2000
DOI: 10.2190/lpcf-p0c3-n4bu-464r
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Theory of Minority Student Participation in Predominantly White Colleges and Universities

Abstract: This article describes the construction of an alternative framework for minority, specifically Chicano, student participation in predominantly White colleges and universities. The framework described is based on a two-year study investigating the experiences and actions of first-generation college students who identify themselves as Chicano. Through interpretation of interviews, observations, and documents, an in-depth understanding of the nature of their experiences and actions on a predominantly White univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…This effect has been reported in some other studies (Snelling et al, ) in which the effect persisted for up to 12 weeks but not others (Hancock et al, ) where religion was reported to be a significant coping mechanism. The root cause of the effect of ethnicity in our population may be that most non‐white non‐Christians were international students who are burdened with a whole host of social and financial stressors that domestic students do not experience (Gonzales, ). Stress associated with cadaver dissection may compound these other stressors resulting in high and sustained anxiety scores on the survey (Evans and Fitzgibbon, ; Dinsmore et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been reported in some other studies (Snelling et al, ) in which the effect persisted for up to 12 weeks but not others (Hancock et al, ) where religion was reported to be a significant coping mechanism. The root cause of the effect of ethnicity in our population may be that most non‐white non‐Christians were international students who are burdened with a whole host of social and financial stressors that domestic students do not experience (Gonzales, ). Stress associated with cadaver dissection may compound these other stressors resulting in high and sustained anxiety scores on the survey (Evans and Fitzgibbon, ; Dinsmore et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these properties influence student satisfaction and the extent to which students take part in educationally purposeful activities (Astin 1977(Astin , 1993bKuh et al 2005b;Kuh et al 1991;Kuh and Whitt 1988;Terenzini 1991, 1995). With this in mind, one school of thought is that student-institution fit models of adjustment such as Tinto's may be framed by culturally biased assumptions about what is necessary to survive and thrive in college (Attinasi 1989(Attinasi , 1992Gonzalez 2000-01;Kuh and Love 2000;Rendon, Jalomo, and Nora 2000;Tierney 1992Tierney , 1993. The point of contention is whether students need or should be expected to conform to prevailing institutional norms and mores if they conflict with those of their family of origin (Tierney 1992).…”
Section: Cultural Perspectivesmentioning
confidence: 99%
“…Taken together, these properties influence student satisfaction and the extent to which they engage in educationally purposeful activities (Astin, 1977(Astin, , 1993bKuh and others, 1991;Kuh, Kinzie, Schuh, Whitt, and Associates, 2005;Kuh and Whitt, 1988;Terenzini, 1991, 1995). From this perspective, student-institution fit models of adjustment such as Tinto's may feature culturally biased assumptions about what is necessary to survive and thrive in college (Attinasi, 1989(Attinasi, , 1992Gonzalez, 2000-01;Kuh and Love, 2000;Rendon, Jalomo, and Nora, 2000;Tierney, 1992Tierney, , 1993. The point of contention is whether students need to or should be expected to conform to prevailing institutional norms and mores if they conflict with those of their family of origin (Tierney, 1992).…”
Section: Cultural Perspectivesmentioning
confidence: 99%
“…It is especially challenging for first-generation students from minority racial and ethnic backgrounds who stand on the margins of two cultures: their friends and family at home and the college community (London, 1989). Many of these students experience going to college as severing important relationships at the same time that they are trying to resolve the conflicts generated by the pressures to succeed educationally and family perceptions that they are rejecting traditional family norms and values by being in college (Gonzalez, 2000-01;Nuñez and Cuccaro-Alamin, 1998;Ortiz, 2004;Torres, 2003). These tensions (often stronger for Latinas, traditionally expected to remain at home) stem not just from simply leaving home, an experience that may not seem as significant to them as actually being away from home.…”
Section: Cultural Perspectivesmentioning
confidence: 99%